2012
DOI: 10.5301/jbm.2012.9346
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative CA-125 predicts extra-uterine disease and survival in uterine papillary serous carcinoma patients

Abstract: Preoperative elevated serum CA-125 is an independent predictor for the presence of extra-uterine disease and an independent risk factor for survival in UPSC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
11
2
Order By: Relevance
“…11,12,14Y19 Since then, several studies have shown associations of elevated CA-125 levels with aggressive histological types of endometrial carcinoma, such as carcinosarcoma 17 and UPSC. 1,6,9,11,20 Nevertheless, the routine use of CA-125 as a preoperative biomarker in UPSC has never been established. The pathological and clinical similarity between UPSC and epithelial ovarian cancer and the wide use of CA-125 in the management of epithelial ovarian carcinoma, as a tumor marker, suggest the possibility of a more specific correlation between tumor levels of CA-125 and UPSC characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12,14Y19 Since then, several studies have shown associations of elevated CA-125 levels with aggressive histological types of endometrial carcinoma, such as carcinosarcoma 17 and UPSC. 1,6,9,11,20 Nevertheless, the routine use of CA-125 as a preoperative biomarker in UPSC has never been established. The pathological and clinical similarity between UPSC and epithelial ovarian cancer and the wide use of CA-125 in the management of epithelial ovarian carcinoma, as a tumor marker, suggest the possibility of a more specific correlation between tumor levels of CA-125 and UPSC characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, according to our data, women with elevated preoperative CA-125 levels may benefit from this comprehensive staging, which has been associated with better survival. 6,20 The retrospective design is a major limitation of this study. Because of the relative rarity of UPSC and the conduct of this study in a single institution, statistical analysis was performed on a small number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olawaiye et al 21 concluded that preoperative serum CA-125 levels correlated with disease stage in patients with USC. Roelofsen et al 22 showed that preoperative CA-125 greater than 45 U/mL remained significantly associated with extrauterine disease (OR, 6.30; 95% CI, 1.93Y20.62) and decreased survival (HR = 3.12; 95% CI, 1.13Y8.73) in USC patients. Abramovich et al 23 concluded that serum CA-125 levels are a useful indicator of disease response or progression in individuals with USC.…”
Section: Discussionmentioning
confidence: 99%
“…Even in apparent clinical early stage disease, USC is found to have unfavorable pathological prognostic factors such as lymphovascular space invasion, lymph node involvement, and microscopic intraperitoneal spread [1,2]. Serum CA125 levels in USC have been assessed in many previous studies [3][4][5][6][7][8][9][10] and their surveillance may be a useful indicator of disease response or progression [9,10] However, data regarding immunohistochemical expression of CA125 in USC tissue are very scarce [11].…”
Section: Introductionmentioning
confidence: 99%